Pectin-based edible coatings formulated with pomegranate peel extracts and other antibrowning agents to extend shelf life of fresh-cut 'Rojo Brillante' persimmon - Taberner, Verònica; Sanchís, Elena; Mateos, Milagros; Palou, Lluís; Pérez-Gago, María B. (ISHS, 2021)
The antioxidant activity and the effects on the physico-chemical and sensory quality of fresh-cut 'Rojo Brillante' persimmon of a pectin-based edible coating formulated with a pomegranate peel extract or other antibrowning agents were compared. Treatments consisted of the pectin-based coating amended with the following anti-browning agents: (1) 15 g kg-1 calcium ascorbate (CaAsc); (2) 10 g kg-1 citric acid (CA) plus 15 g kg-1 CaAsc; (3) 15 g kg-1 aqueous pomegranate peel extract (PG) and (4) 15 g kg-1 PG plus 15 g kg-1 CaAsc. Persimmon slices were dipped in the pectin-based edible coatings or in water (control), packed with macro-perforated film to maintain the ambient atmosphere within the package, and stored at 5°C and 95% RH for up to 9 days. Colour, polyphenol oxidase (PPO) activity, firmness and sensorial quality (visual, overall flavour, off-flavour and firmness) were measured after 2, 5, 7 and 9 days of storage. Coated samples presented lower a* values than control samples, the coatings being amended with PG the most effective to maintain L* during storage, which indicated an effective browning inhibition on fresh-cut persimmon. Only the coatings containing 15 g kg-1 CaAsc significantly reduced PPO activity compared to uncoated samples during 5 days of storage at 5°C. Pectin-based coatings formulated with PG alone or in combination with CaAsc significantly reduced firmness loss of persimmon slices during 5 days of storage at 5°C with respect to control samples. At the end of the storage period, overall flavour was evaluated as excellent for all treatments and fruit were considered neither soft nor firm. Overall, only persimmon slices treated with the coating containing PG and CaAsc were evaluated above the limit of marketability after 7 days of storage.